An investigation into the effect of leadership style on stress-related presenteeism in South African knowledge workers - Reuben George (SA Journal of Human Resource Management, 2017)
Orientation: Leadership styles influence knowledge workers’ job-stress-related presenteeism (JSRP) and, ultimately, organisational performance. Knowledge workers generally work under strict deadlines in fast-paced, stressful environments, and require organisational support.